2014
DOI: 10.1016/j.celrep.2014.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ppk26, a DEG/ENaC Channel Functioning with Ppk1 in a Mutually Dependent Manner to Guide Locomotion Behavior in Drosophila

Abstract: Summary A major gap in our understanding of sensation is how a single sensory neuron can differentially respond to a multitude of different stimuli (polymodality), such as propio- or noci- sensation. The prevailing hypothesis is that different stimuli are transduced through ion channels with diverse properties and subunit composition. In a screen for ion channel genes expressed in polymodal nociceptive neurons we identified Ppk26, a member of the trimeric Degenerin/Epithelial Sodium (DEG/ENaC) channel family a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
117
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 74 publications
9
117
0
Order By: Relevance
“…It is reported that NOMPC is expressed in class I da neurons and bd neurons, and mutations of NOMPC cause prolonged stride duration and reduced crawling speed of mutant larvae (9). In contrast, the DEG/ ENaC ion channels PPK and PPK26 function in class IV da neurons to modulate the extent of linear locomotion; reduction of these channel functions leads to decreased turning frequency and enhanced directional crawling (6,10).…”
Section: Differential Functions Of Different Sensory Neurons In Regulmentioning
confidence: 99%
See 4 more Smart Citations
“…It is reported that NOMPC is expressed in class I da neurons and bd neurons, and mutations of NOMPC cause prolonged stride duration and reduced crawling speed of mutant larvae (9). In contrast, the DEG/ ENaC ion channels PPK and PPK26 function in class IV da neurons to modulate the extent of linear locomotion; reduction of these channel functions leads to decreased turning frequency and enhanced directional crawling (6,10).…”
Section: Differential Functions Of Different Sensory Neurons In Regulmentioning
confidence: 99%
“…The TRPN channel NOMPC functions in class III da neurons to mediate gentle touch sensation (13) whereas the DEG/ENaC ion channels PPK and PPK26, the TRP channel Painless, and Piezo function in class IV da neurons to mediate mechanical nociception (10,20,(46)(47)(48). As to proprioception, chordotonal organs, class I and class IV da neurons and bd neurons may all contribute to proprioception to regulate larval locomotion behavior (5)(6)(7)(8)10). It is reported that NOMPC is expressed in class I da neurons and bd neurons, and mutations of NOMPC cause prolonged stride duration and reduced crawling speed of mutant larvae (9).…”
Section: Differential Functions Of Different Sensory Neurons In Regulmentioning
confidence: 99%
See 3 more Smart Citations